Investigation of Solution Behaviour of Potassium Halides in Aqueous Solution of L- Proline at Different Temperatures: A Physicochemical Approach - Partha Sarathi Sikdar; Pritam De; Firoj Alam; Biswajit Ghosh; Salim Ali; Ayesha Hossain; Antara Sharma; Pranish Bomzan; Kangkan Mallick; Mahendra Nath Roy (Progress in Chemical Science Research Vol. 5, 2022)
An analysis on the molecular interactions of potassium halides in aqueous mixture of L-Proline have been studied by measuring density (\(ρ\)) and viscosity (\(η\)) at three different temperatures (298.15, 308.15 and 318.15 K). Apparent molar volume (\(φ\)v ) and viscosity B-coefficients were derived using Masson equation and Jones-Dole equation respectively and these derived parameters interprets the existing ion-solvent and ion-ion interactions in solution. The structure-making or breaking capacity of the electrolyte under investigation has been discussed in terms of sign of (\(φ\)V0 /\(δ\)T)p.